Essential Oil Composition and Antimicrobial Activities of Two Closely Related Species, Alpinia mutica Roxb. and Alpinia latilabris Ridl., from Peninsular Malaysia - Halijah Ibrahim; Yasodha Sivasothy; Devi Rosmy Syamsir; Noor Hasima Nagoor; Natasha Jamil; Khalijah Awang (The Scientific World Journal)
The essential oils obtained by hydrodistillation of the unripe and ripe fruits of Alpinia mutica Roxb. and Alpinia latilabris Ridl. were analysed by capillary GC and GC-MS. The oils were principally monoterpenic in nature. The unripe and ripe fruit oils of A. mutica were characterized by camphor (21.0% and 15.8%), camphene (16.6% and 10.2%), β-pinene (8.6% and 13.5%), and trans,trans-farnesol (8.0% and 11.2%), respectively. The oils of the unripe and ripe fruits were moderately active against Staphylococcus aureus, Bacillus subtilis, Trichophyton mentagrophytes, and Trichophyton rubrum. 1,8-Cineole (34.2% and 35.9%) and β-pinene (20.2% and 19.0%) were the two most abundant components in the unripe and ripe fruit oils of A. latilabris. The oil of the unripe fruits elicits moderate activity against Staphylococcus aureus and Trichophyton mentagrophytes while Candida glabrata was moderately sensitive to the oil of the ripe fruits.